STRATEGI IKEA DALAM MEWUJUDKAN BISNIS BERKELANJUTAN PADA PENGGUNAAN KAPAS TAHUN 2015-2022 - Afissa Hanani Oktavia; Adiasri Putri Purbantina (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2023)
Sustainable business practices are a form of responsibility for multinational companies in the midst of commitments to implement SDGs by countries affected by business expansion in running their production systems. In carrying out its business operations, IKEA continues to uphold business operation standards with continuous innovation. This company has adopted a sustainable business innovation model called IWAY Standard to fulfill its commitment to implementing SDGs in the industrial and agricultural sectors, especially in the use of cotton. This research uses a qualitative descriptive method and focuses on case studies to describe and analyze the implementation of the IWAY Standard in meeting the needs of IKEA cotton raw materials sourced from supplier countries. The data used in this research is secondary data using the Sustainable Business Model Innovation (SBMI) approach which is used to identify the implementation of the IWAY Standard in the use of sustainable cotton by IKEA from 2015 to 2022. The results of this research show that through the sustainable business strategy realized in IWAY Standard, the multinational company IKEA has carried out its environmental, social and economic responsibilities through three SBMI components, namely Sustainable Value Propositions Innovation, Sustainable Value Creation & Delivery, and Sustainable Value Capture Innovation which have been implemented by IKEA. These include program collaboration, solving sustainability problems, developing products and services, ratifying policies, organizing companies in a sustainable manner, building positions in tandem with stakeholders, as well as designing new sustainable income models and cost structures. Keywords: Sustainable Business; IKEA; IWAY Standard; Cotton Raw Materials; and Business Innovation.